Improving the Mechanical Properties of Salt Core through Reinforcing Fibers - 류아롬; 류소연; 전민석; 김동균; 홍기원; 남산; 최지원 (한국센서학회, 2023)
Salt cores have attracted considerable attention for their application to the casting process of electric vehicle parts as a solution to ecological issues. However, the salt core still has low mechanical strength for use in high-pressure die casting. In this study, we investigated the improvements in the bending strength of KCl-based salt cores resulting from the use of reinforcing materials. KCl and Na2CO3 powders were used as matrix materials, and glass fiber and carbon fiber were used as reinforcing materials. The effects of carbon fiber and glass fiber contents on the bending strength properties were investigated. Here, we obtained a new fiber-reinforced salt core composition with improved bending strength for high-pressure die casting by adding a relatively small amount of glass fiber (0.3 wt%). The reinforced salt core indicates the improved properties, including a bending strength of 49.3 Mpa, linear shrinkage of 1.5%, water solubility rate of 16.25 g/min·m2 in distilled water, and hygroscopic rate of 0.058%.